Peningkatan Strategi Minat Kunjung terhadap Pemanfaatan Bahan Koleksi Anak di TBM Luckman Sinar Medan - Yusniah Yusniah; Zaki Fahri; Rahma Sariva; Iyen Supit; Juni Ervina Sari Harahap; Ikbal Fauzi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
Community Reading Centers (TBM) are facilities established for reading that offer reading material services in the form of: books, magazines, tabloids, newspapers, comics, and other multimedia materials. The Tengku Luckman Sinar community reading center has a collection of books on history, art, culture, law, novels and encyclopedias. The management of the Tengku Luckman Sinar reading garden has not been fully implemented properly. This study aims to see or know visits to children's reading interest and the use of children's reading collections at TBM Tengku Luckman Sinar which has provided a large collection of books. This study uses a qualitative research methodology that uses primary data. The results of this study are that Luckman Sinar TBM is still constrained by the problem of low funding, which is the biggest obstacle for this TBM library/facility. TBM admits that it does not have any funds, including TBM Tengku Luckman Sinar, and continues to use the funds used by TBM as personal funds. Evaluation of the library's financial strategy is a measurement and evaluation of the impact of financial measures that compare the results achieved with the goals set. Keywords: Community Reading Park, Children's Reading Collection Material